1996
DOI: 10.1021/cm960177l
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy of Ordered Arrays of Heteropolyacids Deposited on a Graphite Surface

Abstract: PMo 12 O 40 , x ) 1, 2, 2.5, 3) deposited on highly oriented pyrolytic graphite (HOPG) surfaces were successfully imaged by scanning tunneling microscopy (STM). All of these heteropoly acids (HPAs) formed clear twodimensional ordered arrays on graphite, and their periodicities were in good agreement with values determined by X-ray crystallography. Spatially resolved tunneling spectroscopy was used to demonstrate that the arrays imaged represented HPA monolayers, as the characteristic tunneling spectrum of grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 30 publications
10
71
1
Order By: Relevance
“…The absence of such variations among different regions of the same sample probed by STM and TS suggests that the composition of the surface HPA arrays is spatially uniform. In agreement with other STM reports, 10,18 the TS measurements also indicated that the HPAs formed monolayers on the graphite surfaces, as the tunneling spectrum of graphite was obtained at high symmetry interstitial sites in these arrays.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of such variations among different regions of the same sample probed by STM and TS suggests that the composition of the surface HPA arrays is spatially uniform. In agreement with other STM reports, 10,18 the TS measurements also indicated that the HPAs formed monolayers on the graphite surfaces, as the tunneling spectrum of graphite was obtained at high symmetry interstitial sites in these arrays.…”
Section: Introductionsupporting
confidence: 92%
“…10,[15][16][17][18][19][20] In tunneling spectroscopy experiments, we have consistently observed that HPAs deposited on graphite exhibit distinctive current-voltage (I-V) behavior, referred to as negative differential resistance (NDR). 10,[18][19][20] In this work, several water-soluble and water-insoluble cationexchanged 12-molybdophosphates were prepared and deposited on a highly oriented pyrolytic graphite (HOPG) surface to obtain images and tunneling spectra by STM. These data serve to establish a correlation between NDR behavior in the tunneling spectrum of the HPA monolayer and its reduction potential, i.e., the oxidizing power of the heteropoly acid catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Literature survey shows that the particles of Cs-salts obtained by the precipitation from aqueous solutions are in the form of irregular aggregates of size within wide range [33,34]. This shape is also observed for our Cs2-CO 3 and Cs2-Cl samples.…”
Section: Cs-salts Of H 3 Pw 12 O 40supporting
confidence: 82%
“…Calibration procedures for the STM measurements are described elsewhere. 35,36 No STM image presented in this report has been filtered, and all lattice dimensions reported were determined from two-dimensional fast fourier transforms (2-D FFT).…”
Section: Methodsmentioning
confidence: 99%